Trajectories of Online Racial Discrimination and Psychological Functioning Among African American and Latino Adolescents. Issue 5 (14th January 2020) - Tynes, Brendesha M.; English, Devin; Del Toro, Juan; Smith, Naila A.; Lozada, Fantasy T.; Williams, David R.
Abstract : This study investigated trajectories of individual and vicarious online racial discrimination (ORD) and their associations with psychological outcomes for African American and Latinx adolescents in 6th–12th grade ( N  = 522; M grade  = 9th) across three waves. Data were analyzed using growth mixture modeling to estimate trajectories for ORD and to determine the effects of each trajectory on Wave 3 depressive symptoms, anxiety, and self‐esteem. Results showed four individual and three vicarious ORD trajectories, with the majority of participants starting out with low experiences and increasing over time. Older African American adolescents and people who spend more time online are at greatest risk for poor psychological functioning.